The G20 and Food Security: A Mismatch in Global Governance? - Jennifer Clapp; Sophia Murphy (Global Policy, 2013)
When the G20 took up food security in 2010, many were optimistic that it could bring about positive change by addressing structural problems in commodity markets that were contributing to high and volatile food prices and exacerbating hunger. Its members could tighten the regulation of agricultural commodity futures markets, support multilateral trade rules that would better reflect both importer and exporter needs, end renewable fuel targets that diverted land to biofuels production, and coordinate food reserves. In this article, we argue that although the G20 took on food security as a focus area, it missed an important opportunity and has shown that it is not the most appropriate forum for food security policy. Instead of tackling the structural economic dimensions of food security, the G20 chose to promote smoothing and coping measures within the current global economic framework. By shifting the focus away from structural issues, the G20 has had a chilling effect on policy debates in other global food security forums, especially the UN Committee on World Food Security (CFS). In addition, the G20 excludes the voices of the least developed countries and civil society, and lacks the expertise and capacity to implement its recommendations.